Factors to predict the knowledge, attitude and practice of nursing interruptions among nurses: A nationwide cross-sectional survey. (October 2022) - Li, Jie; Wang, Sha; Wu, Xiaoqi; Liu, Min; Gan, Gang; Dong, Xiaoqian; Fu, Yajuan; Xie, Jianfei; Cheng, Andy SK
Abstract: Aim: To identify the knowledge, attitude and practice of nursing interruptions and related factors among nurses in China. Background: Nursing interruptions are extremely common and have introduced major security risks and harm to hospitalized patients. However, nursing interruptions' factors are not well known. Design: A nationwide cross-sectional descriptive survey. Methods: A multistratified random sampling method was used to obtain nurses from five provinces in China. We collected data by online questionnaires (the Knowledge, Attitude and Practice Questionnaire of Nursing Interruptions, the Chinese Revised Safety Attitude Questionnaire and the Coping Adaptation Processing Scale). We used the Mann–Whitney test, the Kruskal-Wallis test, Spearman's linear correlation analysis and multiple linear stepwise regression to analyze the data. A STROBE checklist was used to report the results. Results: Of the 14500 questionnaires distributed, 14302 (98.6 %) were returned. The mean score was 79.69 (SD 17.73) and the level was medium. Having attended nursing interruptions training and attended nursing safety training, safety attitude, coping ability and position were positive factors, while age and marital status were negative factors (F=1068.226, p < 0.001, R 2 =0.374, adjusted R 2 =0.373). Conclusions: Chinese nurses expressed a moderate level of knowledge, attitude and practice of nursing interruptions. Safety attitude, having attended nursing interruptions training, coping ability, having attended nursing safety training, position, age and marital status were predictors. Relevance to clinical practice: Nursing managers should pay attention to the influencing factors of clinical nurses' knowledge, attitude and practice of nursing interruptions and take effective individualized training for clinical nurses with different ages, positions and marital status to improve their coping ability, so as to ensure nursing safety and improve nursing quality.